Simultaneous Expression of UV and Violet SWS1 Opsins Expands the Visual Palette in a Group of Freshwater Snakes. (25th September 2021) - Hauzman, Einat; Pierotti, Michele E R; Bhattacharyya, Nihar; Tashiro, Juliana H; Yovanovich, Carola A M; Campos, Pollyanna F; Ventura, Dora F; Chang, Belinda S W
Abstract: Snakes are known to express a rod visual opsin and two cone opsins, only (SWS1, LWS), a reduced palette resulting from their supposedly fossorial origins. Dipsadid snakes in the genus Helicops are highly visual predators that successfully invaded freshwater habitats from ancestral terrestrial-only habitats. Here, we report the first case of multiple SWS1 visual pigments in a vertebrate, simultaneously expressed in different photoreceptors and conferring both UV and violet sensitivity to Helicops snakes. Molecular analysis and in vitro expression confirmed the presence of two functional SWS1 opsins, likely the result of recent gene duplication. Evolutionary analyses indicate that each sws1 variant has undergone different evolutionary paths with strong purifying selection acting on the UV-sensitive copy and d N / d S ∼1 on the violet-sensitive copy. Site-directed mutagenesis points to the functional role of a single amino acid substitution, Phe86Val, in the large spectral shift between UV and violet opsins. In addition, higher densities of photoreceptors and SWS1 cones in the ventral retina suggest improved acuity in the upper visual field possibly correlated with visually guided behaviors. The expanded visual opsin repertoire and specialized retinal architecture are likely to improve photon uptake in underwater and terrestrial environments, and provide the neural substrate for a gain in chromatic discrimination, potentially conferring unique color vision in the UV–violet range. Our findings highlight the innovative solutions undertaken by a highly specialized lineage to tackle the challenges imposed by the invasion of novel photic environments and the extraordinary diversity of evolutionary trajectories taken by visual opsin-based perception in vertebrates.